Designing a Solar Cooking System Integrated with PCM (Phase Change Material): Modelling and Economic Feasibility for Rural Communities of Pakistan - Hassan, Taymoor (319861); Dr. Mariam Mahmood (USPCAS-E, NUST,Islamabad, 2023)
TH-487
Keywords: MS Thesis; MS-TEE Thesis